2010
DOI: 10.5005/jp-journals-10015-1001
|View full text |Cite
|
Sign up to set email alerts
|

Dental Infection Control in India at the Turn of the Century

Abstract: The purpose of this study was to assess the status of Dental Infection Control and Occupational Safety in India. 456 respondents (dentists) used this self-administered survey instrument containing about 96 variables. Over 95% of respondents felt that HIV and Hepatitis were infectious disease risks of concern and that infectious diseases were on the rise in India. Education and training in Dental Safety were lacking and that the latter are made mandatory in dental school curricula. Availability and access to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In contrast to the case in developed countries, in developing countries affordability, unavailability, limited resources and shortage of equipment have been put forward as reasons for low compliance with PPE guidelines 45,47,51 .…”
Section: Focus Area Three: Personal Protective Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the case in developed countries, in developing countries affordability, unavailability, limited resources and shortage of equipment have been put forward as reasons for low compliance with PPE guidelines 45,47,51 .…”
Section: Focus Area Three: Personal Protective Equipmentmentioning
confidence: 99%
“…Findings from India indicated that many practitioners used autoclaves 47 . However, the results from this study revealed that the majority used locally manufactured pressure cookers for sterilisation and thus never packed instruments for sterilisation and storage 47 . Further reports from India also indicated that many dentists (71%) used boiling water as the sterilising medium 26 .…”
Section: Focus Area Five: Sterilisationmentioning
confidence: 99%
“…56% of respondents stated that all patients should be treated as potentially infectious (while a 100% of patients should have been viewed as potentially infectious) which is in contrast to study done by Puttaiah etal (7) where 66% felt the same indicating the need for continuous dental education programmes stressing the importance of infection control and safety guidelines.…”
Section: Discussionmentioning
confidence: 64%
“…It showed that dental interns had better awareness than medical interns (6). And a study conducted in 2010 among dentists to assess the status of Dental Infection Control and Occupational Safety in India showed that even though dentists had adequate knowledge in the subject of infectious diseases, attitude (Stigma) towards treating infected patients was a negative factor (7). However, as they are few studies done exclusively among dental students the present study was done to explore their awareness on blood-borne exposures and prevalence as well from start of their clinical training.…”
Section: Introductionmentioning
confidence: 93%
“…The various literature suggests that dental personnel and the dental students are not aware of a laid down protocol for infection control. 8 Although there have been clear protocol from the Western countries, 2 the Indian dental fraternity is far behind in terms of compliance to these policies. 8 Literature suggests that training for dental personnel in infection control has to be undertaken as mandatory in order to attain effective compliance to infection control procedures.…”
Section: Introductionmentioning
confidence: 99%